2014
DOI: 10.1021/jm500801r
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Structure–Activity Relationship Studies of a Series of [4-(4-Carboxamidobutyl)]-1-arylpiperazines: Insights into Structural Features Contributing to Dopamine D3 versus D2 Receptor Subtype Selectivity

Abstract: Antagonist and partial agonist modulators of the dopamine D3 receptor (D3R) have emerged as promising therapeutics for the treatment of substance abuse and neuropsychiatric disorders. However, development of druglike lead compounds with selectivity for the D3 receptor has been challenging because of the high sequence homology between the D3R and the dopamine D2 receptor (D2R). In this effort, we synthesized a series of acylaminobutylpiperazines incorporating aza-aromatic units and evaluated their binding and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 74 publications
(177 reference statements)
0
30
0
Order By: Relevance
“…In addition, these compounds also display receptor-blocking properties [15][16][17][18][19]. Moreover, arylpiperazine derivatives have been reported as anticancer drugs for site-directed chemotherapy of prostate cancer in our previous work [20,21], and some derivatives showed significant cytotoxic activity against the tested prostate cancer cell lines.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, these compounds also display receptor-blocking properties [15][16][17][18][19]. Moreover, arylpiperazine derivatives have been reported as anticancer drugs for site-directed chemotherapy of prostate cancer in our previous work [20,21], and some derivatives showed significant cytotoxic activity against the tested prostate cancer cell lines.…”
Section: Discussionmentioning
confidence: 93%
“…However, administration of two different selective antagonists of D3 receptors, SB‐277011‐A and SR‐21502, did not influence the aforementioned tremorlytic effects of pramipexole and 7‐OH‐DPAT. Both these compounds bind to dopamine D3 receptors with low nanomolar affinities ~ 100 times higher than to D2 receptors . The doses of SB‐277011‐A and of SR‐21502, as well as times of their injections before tremor measurements, were chosen according to previous studies which showed that they occupied >90% D3, but no D2 receptors in vivo , and/or induced several pharmacological effects in rats .…”
Section: Discussionmentioning
confidence: 99%
“…Two selective antagonists of dopamine D3 receptors: (1) SB‐277011‐A [trans‐ N ‐[4‐[2‐(6‐cyano‐1,2,3,4‐tetrahydroisoquinolin‐2‐yl)ethyl]cyclohexyl]‐4‐quinolinicarboxamide] dihydrochloride (Abcam; 10 mg/kg ip ) and (2) SR‐21502 [ N ‐(4‐(4‐(2‐(tert‐butyl)‐6‐(trifluoromethyl)pyrimidin‐4‐yl)piperazin‐1‐yl)butyl)imidazol[1,2‐α]pyridine‐2‐carboxamide] dihydrochloride (Southern Research Institute, Birmingham, AL, USA; 15 mg/kg ip ) , a nonselective antagonist of dopamine D2‐like receptors, haloperidol (Warszawskie Zakłady Farmaceutyczne, Polfa, Warszawa, Poland, ampules a 5 mg/1 mL aqua pro injectione; 0.5 mg/kg ip ), and an antagonist of presynaptic D2/D3 autoreceptors, amisulpride (Tocris Bioscience, Bristol, UK; 1 mg/kg ip ) , were used. Physiological saline was used for all control injections.…”
Section: Methodsmentioning
confidence: 99%
“…53 For this study, 8 was prepared by a modified synthesis as follows: To a suspension of 4-( tert -butyl)-6-(piperazin-1-yl)-2-(trifluoromethyl)pyrimidine (1.0 g, 3.46 mmol), K 2 CO 3 (0.96 g, 6.92 mmol) and KI (cat.) in anhydrous acetonitril (30 mL) was added 4-bromobutyronitrile (3.46 mmol, 0.35 mL) and the reaction mixture was refluxed for 16 h. After cooling to room temperature it was quenched by the addition of water and the aqueous phase was extracted with DCM (3x).…”
Section: Methodsmentioning
confidence: 99%